Depressive symptoms as a predictor of rehospitalization and death of heart failure - Pena, Felipe Montes; das Chagas, Renato Teresa; Soares, Jamil da Silva; Pena, Maria Angela Montes Belo (Open Science Journal, 2023)
Introduction: Hearth failure is a disease with a high risk of complications and reduces life expectancy. Ventricular function and neurohumoral activation are defining characteristics of the disease. The present of depressive symptoms is extremely common and determinant for the HF, and its influence may determine the prognosis of the disease. Methods: Consecutively hospitalized patients with HF were analyzed and recruited for three months, receiving clinical follow-up for six months after admission. Sociodemographic and clinical variables were analyzed and submitted to a type II Beck questionnaire to analyze depressive symptoms. They received clinical follow-up in person or by phone call to determine whether there was hospital readmission or death in the afore mentioned period. Chi-square test, Student’s t-test were used to compare groups with and without depressive symptoms, multivariate analysis was used to determine mortality predictors in the group with depressive symptoms up to the sixth month. Results: Initially, 103 patients were included, and after six months 96 patients remained alive. The mean age was 63.5±12.1 years. Most patients were female (58.4%). New York Heart Association functional class was in II and III in 75% of the sample. In the sample, 59 (61.4%) had DS by the Beck questionnaire type II. There were 28 (29.2%) patients with the analyzed outcomes and in the multivariate logistic regression analysis, the presence of age was a determining factor for the outcomes. Conclusion: The presence of heart failure associated with depressive symptoms becomes a combination with increasingly evident complications, as well as it also becomes a long-term relevant factor for readmission and death. Depressive symptoms in our sample proved to be a major factor in deaths and readmissions. A multidisciplinary care is extremely important for the improvement of care.